Effects of rotary mower blade cutting angles on the pulverization of sweet potato vine - Kakahy, Amer N. N.; Ahmad, Desa; Akhir, M. D.; Sulaiman, Shamsuddin; Ishak, Aris (Elsevier, 2014)
A rotary mower with five different blade cutting angles was tested at five different cutting speeds to determine the resultant pulverized percentage of sweet potato vine (< 28 mm) and the power consumed (Joule). The best results for effects of interaction between blade angles and mower speeds was achieved by the 30° blade angle at 2440 rpm with highest percentage of pulverized vine at 61.27% while the best performance for effects of interaction between blade angles and mower speeds was achieved by the 30° blade angle at 1830 rpm with lowest power consumption of 44.00 Joule.